Techniczne uzbrojenie pracy a akumulacja w gospodarstwach chłopskich - Wiatrak, Andrzej Piotr (Wydział Prawa i Administracji UAM, 1979)
Accumulation in individual farms is closely connected with level of technical labour equipment and it generally increases when this level grows. Increase in technical labour equipment causes growth of accumulation in a farm and for one person employed. It is true for all groups of farms but the degree of growth is different. It increases quickly at the beginning, then the rate of accumulation growth is smaller. The growth is the most significant in farms characterized by the highest level of technical labour equipment. The growth is, however, irregular and it occurs stepwise in dependence on combination of production factors and methods used. It finds reflection in comparison of interdependence between technical labour equipiment and accumulation when re-calculated for a hectare of arable land. This relation attains a high value in farms with the weakest equipment with fixed capital. In turn, in other groups of farms the accumulation level re-calculated for a unit of area is lower, but it shows a growing tendency. The accumulation susceptibility calculated for a hectare of arable land is the highest in farms best provided with production means. The process of growth runs then in accordance with a character of introducing and changing production techniques. It determines simultaneously the accumulation susceptibility and its share in farm and personal incomes in particular groups of farms according to technical labour equipment.
Technical Work Equipment and Accumulation in Individual Farms